Effect of testosterone therapy on migraine frequency and disability in two transgender patients: a case report. Issue 1 (24th January 2023) - Todd, Candice Marie; Yu, Amy; Lay, Christine; Lagman-Bartolome, Ana Marissa
Abstract : With an increasing number of patients seeking gender-affirming hormone therapy (GAHT), the clinical impact of testosterone treatments on headache needs to be determined. Our case report looks at the potential effect of testosterone on migraine among transgender patients. We present two transmasculine patients who used masculinising hormone therapy with testosterone. Both patients described their headache as moderate-to-severe pain with features that fulfilled the criteria for chronic migraine without aura. Following GAHT, one patient improved in both frequency and intensity of headache symptoms while the other noted improvement in headache intensity alone. Our report postulates that testosterone therapy may have a positive impact on headaches in individuals participating in GAHT, highlighting the need for further research on the role of testosterone therapy on headache in transmasculine individuals.